SambalTempeLit / Siti Hajar Abdul Malek and Ummi Ruwaidah Rosman - Abdul Malek, Siti Hajar; Rosman, Ummi Ruwaidah (2022)
The proposed sale of Sambal tempe Lit is a joint idea between Siti Hajar Abdul Malek and Ummi Ruwaidah Rosman. Both of us plan to sell something simple as we are bot first-time-entrepreneurs doing business either physically or online. The choice of Sambal Tempe Lit as the product name is from a suggestion from Siti Hajar in making it easier for customers to recognize our product only by its name. The choice of color in the logo which is bright yellow, is also one of our marketing methods in attracting of food lovers by using bright colors. We decide to create simple food because food is the product that is easy to sell. We started the sales by giving a tester to our closest friends. At first, we brought the Sambal Tempe as snack during study time and during iftar. From there, our friends are interested to know more about our products and provide some comments that we can take as an improvement of the quality of our product.